Pain Management Concerns From the Hospice Family Caregivers' Perspective. (April 2018) - Chi, Nai-Ching; Demiris, George; Pike, Kenneth C.; Washington, Karla; Oliver, Debra Parker
Background: Pain management is a challenging task for family caregivers in home hospice care. However, there are limited studies that examine the challenges regarding pain management in hospice care from family caregivers' perspectives. Objectives: To identify the challenges related to pain management faced by family caregivers in hospice care and to examine the validity of an existing framework that outlines pain management challenges for hospice family caregivers. Design: We conducted a theory-driven, deductive content analysis of secondary data obtained from hospice family caregivers' interviews from a randomized clinical trial. Setting/Participants: We included baseline interviews of 15 hospice caregivers of patients from hospice agencies in the States of Washington. The majority of the participants were white and female caregivers. They were spouse/partner or adult child living with the patient. Results: The study identified 5 out of the 6 major themes in the original framework and confirmed that hospice family caregivers face a variety of challenges: caregiver-centric issues, caregiver's medication skills and knowledge, communication and teamwork, organizational skill, and patient-centric issues. A couple of the subthemes in the original framework were not present in our findings. We also expanded the original framework by adding 1 subtheme and revised 2 definitions in the original framework. Conclusion: The study provided an investigation on hospice family caregivers' difficulties in pain management. The results can inform health-care providers and researchers of family caregivers' challenges and provide insights for future designs of educational tools targeting pain management strategies, so that family caregivers can perform pain management effectively at home.